Sejarah dan Perkembangan Bahasa Indonesia (Ditinjau dari Perspektif Sejarah Bahasa Indonesia) - Fadhelin, Elfiza; Yulyansari , Eli; Olivia , Indi; Yopitasari , Nesy; Safitri , Riska Aulia; Yuniati, Ira; Yulinda, Ade Tiara (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The current of globalization and the development of information technology have increased the use of foreign languages ​​in various fields of life, thus creating challenges to maintaining the existence of Indonesian as a national language and state language. This condition encourages the importance of studying the efforts that have been made to maintain the function, status, and development of Indonesian. This study aims to analyze the role of the Indonesian Language Congress in maintaining the existence of Indonesian amidst the development of globalization and modernization. The study uses a library research method by reviewing various scientific sources, official documents, laws and regulations, and publications regarding the implementation of the Indonesian Language Congress. Data are analyzed descriptively through the process of reduction, grouping, interpretation, and drawing conclusions from information obtained from various sources. The results of the study indicate that the Indonesian Language Congress plays a strategic role in formulating language policies, developing vocabulary, fostering and protecting Indonesian, and strengthening the function of Indonesian as a language of science, education, and national communication. Thus, the Indonesian Language Congress is an important instrument in supporting the continued existence of Indonesian so that it remains adaptive to developments in science, technology, and global dynamics.